Risk-Adjusted Credit Pricing: Application to the state’s guarantee funds for Moroccan enterprises - OUSSOUADI , Kamal; CHERKAOUI, Kenza (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Authorities’ intervention is key to facilitating access to sources of finance for small and medium enterprises (SMEs). Credit guarantee is a viable solution that is more conducive to bringing the financing needs of SMEs closer to the demands of the financial sector. However, the sustainability of any guarantee system depends on its ability to balance between its resources and its jobs, i.e. the equality between the indemnifications of the losses due to credit risk on the one hand and the commissions, the investment products and laps on the other side. As a result, the fee structure of the guarantee commission must be able to cover a part of the financial charges resulting from the operation of the guarantee of the credits, namely the cover of the credit risk and the management cost. This work introduces a new approach to assess the cost of the guarantee taking into account the cost of credit risk and the cost of management.